Birth of American Football, the Death Sentence to Rugby in America - Swick, Jeremy (My University, 2014)
This research attempts to discover why American football took a prominent hold in the United States and rugby did not. American football rose in popularity while rugby never was able to grasp a lasting stronghold on the United States not due to one specific event, but to a multitude of different factors. Early rugby was considered too dangerous to be played, and the rules were changed, thus giving birth to American football. Rugby in Europe also made changes to adopt a more acceptable game. Once these early rules were changed, football in America began to rise in popularity, and the Eastern and Midwestern parts of the United States opted to adopt American football. Not satisfied with these rule changes, the Western parts of the United States opted to adopt the English rugby style of play, as the early rugby game had been reformed in Europe as well. Despite initial success in the West, it was clear the United States was not on the same playing field in rugby as the rest of the world. Many saw football as America's emerging pastime and believed all of the United States should play the same contact sport. The final death sentence for rugby in the United States was the 1924 Olympics. Despite the United States defeating the host nation, France, the aftermath following the gold medal game sealed the fate for rugby in America in the 20th century.
Keywords: Olympics; Rugby football